2018
DOI: 10.1111/bju.14366
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of magnetic resonance imaging for tumour staging of bladder cancer: systematic review and meta‐analysis

Abstract: The purpose of this study is to evaluate accuracy of magnetic resonance imaging (MRI) for local staging of bladder cancer for four clinical scenarios (T-stage thresholds) considered against current standards for clinical staging and secondarily to identify sources for variability in accuracy. Systematic review of patients with bladder cancer undergoing T-staging MRI to evaluate the diagnostic accuracy using bivariate random-effects meta-analysis. Sub-group analysis was done to explore variability; risk of bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 26 publications
(35 reference statements)
3
58
0
1
Order By: Relevance
“…However, its diagnostic accuracy is less than satisfactory, with a reported range between 64.7% and 83% . Although other sequences, such as diffusion‐weighted and dynamic contrast‐enhanced imaging, are proposed to assist the local staging of BCa, a recent meta‐analysis revealed that there was no significant difference in the accuracy of discrimination between MIBC and NMIBC . Currently, there currently insufficient data on the use of diffusion‐weighted imaging in MIBC to allow for a recommendation to be made in the guidelines .…”
Section: Introductionmentioning
confidence: 99%
“…However, its diagnostic accuracy is less than satisfactory, with a reported range between 64.7% and 83% . Although other sequences, such as diffusion‐weighted and dynamic contrast‐enhanced imaging, are proposed to assist the local staging of BCa, a recent meta‐analysis revealed that there was no significant difference in the accuracy of discrimination between MIBC and NMIBC . Currently, there currently insufficient data on the use of diffusion‐weighted imaging in MIBC to allow for a recommendation to be made in the guidelines .…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Parikh et al, this technique, which employed free‐breathing continuous acquisition without a predetermined temporal resolution (which can be later reconstructed at various temporal resolutions from source data) using compressed sensing with radial acquisition (GRASP, Siemens Healthcare) achieved high‐quality imaging at varying temporal resolutions during simultaneous MRU . The added value of DCE in addition to DWI and T 2 W sequences for the local staging of bladder cancer is unclear, and there are limited data directly comparing the individual mp‐MRI sequences …”
Section: Mri Techniquementioning
confidence: 99%
“…The manifestation of each T stage depends on the MRI sequence, with different features for T 2 W images, DCE images, and DWI (Table ). Multiple studies suggest that the accuracy of MRI for determining bladder cancer T stage is optimized when using all three of these sequences together (mp‐MRI); however, a recent meta‐analysis found that there was no significant difference in accuracy of discrimination between non‐MIBC and MIBC, and between the absence and presence of peri‐vesical invasion, using different MRI techniques …”
Section: Mri Staging and Accuracymentioning
confidence: 99%
See 2 more Smart Citations